(untitled) (Global Journal of Science Frontier Research, 2017)
The present paper deals with the study of pseudo Ricci symmetric properties on (LCS)n-manifolds. Here we study generalized pseudo Riccisymmetric, almost pseudo Riccisymmetric and semi pseudo Ricci-symmetric (LCS)n-manifolds and obtained some interesting results.